Structural Composition and Diversity of Bacterial Communities in High- and Low-Yielding Moso Bamboo Forests - Zongsheng Yuan; Fang Liu; Yue Yuan; Hui Pan (Frontiers in Bioscience-Landmark, 2023)
Background: Bacterial communities play an important role in helping plants absorb nutrients, promoting plant development, and preventing diseases. Moso bamboo (Phyllostachys edulis [Carriere] J. Houzeau) has a long history of cultivation and important economic value. Methods: In this study, high-throughput sequencing technology was utilized to analyze the differences in the diversity of endophytic and root zone soil bacterial communities between high-yielding (HY) and low-yielding (LY) P. edulis forests in subtropical China. Results: Notably, the soil conditions and bacterial communities in Yong’an (YA) and Jiangle (JL) differed, but the bacterial community structures in the root zone soil of both regions were similar with the dominant bacterial phyla composed of Proteobacteria, Acidobacteriota, and Actinobacteriota. The Chao1 and Shannon indices of the root zone soil and endophytic bacterial communities in the LY were higher than those in the HY. Moreover, the bacterial community structures of HY and LY were significantly different. Notably, the relative abundances of Actinobacteriota, Myxococcota, and Cyanobacteria were higher in the HY soil samples. The bacterial community differences between the tissues and root zone soil of HY and LY indicated that healthy HY P. edulis plants were enriched with specific bacterial communities, suggesting associations between yield and both endophytic and root zone soil bacterial communities. Conclusions: The findings of this study provide a basis to regulate artificial bacterial communities to benefit the future cultivation of HY P. edulis.